Abnormal pupils’ reactions - Kowal, Joanna; Strzałka, Anna; Kubicka-Trząska, Agnieszka; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Examination of the pupils’ light reaction and estimation of the pupils’ diameter are the components of the routine physical examination of a patient. Disturbances in pupils’ light reaction, unequal size of the pupils indicate damage of the nervous system and require careful diagnosis, both neurological and ophthalmological. Different aspects of anatomy, physiology and the most common pathological syndromes associated with disturbed pupils’ light reaction and unequal diameters of the pupils were presented in the article. Early diagnosis and proper treatment can allow to improve prognosis in the analyzed patient group.